Implementasi Pendidikan Karakter Berbasis Pesantren dalam Pembelajaran Pendidikan Agama Islam - Sidik, Muhamad Fajar; Khoiruddin, M. Arif (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2022)
This research is motivated by the reality of today's education. The decline in the quality of education that pays less attention to the character education of students which results in the decline of the morality of the younger generation, some actions that are not in accordance with values ​​and norms have become commonplace, such as brawls, juvenile delinquency, cheating, and so on. Therefore it is necessary to integrate the values ​​of character education, especially in the learning process of Islamic religious education which incidentally has the aim of forming akhlaqul karimah. This research includes questions. How to plan, implement, and evaluate Islamic boarding school-based character education in PAI learning.The implementation of character education in Islamic religious education learning at pesantren-based schools at SMK Al-Mahrusiyah is carried out in the planning stage by making a syllabus and lesson plans by inserting character values ​​in each learning material. The implementation is by integrating character values ​​into all PAI materials. Then an evaluation is held to assess the child's character. carried out include tests and non-tests. Evaluation by means of tests to determine the extent of cognitive abilities. while the non-test evaluation is assessed from the daily lives of students.